2005
DOI: 10.1038/nn1458
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid signaling depends on the spatial pattern of synapse activation

Abstract: The brain's endocannabinoid retrograde messenger system decreases presynaptic transmitter release, but its physiological function is uncertain. We show that endocannabinoid signaling is absent when spatially dispersed synapses are activated on rodent cerebellar Purkinje cells but that it reduces presynaptic glutamate release when nearby synapses are active. This switching of signaling according to the spatial pattern of activity is controlled by postsynaptic type I metabotropic glutamate receptors, which are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
135
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(152 citation statements)
references
References 25 publications
15
135
2
Order By: Relevance
“…Hashimotodani et al (2005) at our laboratory have revealed that this cooperativity is attributable to PLCb activity that depends on both intracellular Ca 2C and G q/11 protein. In cerebellar Purkinje cells, a brief burst of parallel fibre stimulation causes mGluR1 activation and local Ca 2C elevation due to AMPA receptor-mediated depolarization, and induces endocannabinoid-mediated retrograde suppression of glutamate release from parallel fibres Brown et al 2003;Marcaggi & Attwell 2005. We have demonstrated that this suppression results from the Ca 2C dependency of PLCb4 .…”
Section: Endocannabinoid Signalling (A)mentioning
confidence: 71%
“…Hashimotodani et al (2005) at our laboratory have revealed that this cooperativity is attributable to PLCb activity that depends on both intracellular Ca 2C and G q/11 protein. In cerebellar Purkinje cells, a brief burst of parallel fibre stimulation causes mGluR1 activation and local Ca 2C elevation due to AMPA receptor-mediated depolarization, and induces endocannabinoid-mediated retrograde suppression of glutamate release from parallel fibres Brown et al 2003;Marcaggi & Attwell 2005. We have demonstrated that this suppression results from the Ca 2C dependency of PLCb4 .…”
Section: Endocannabinoid Signalling (A)mentioning
confidence: 71%
“…Crosstalk between synapses-i.e., summation of glutamate released from neighboring synapses-is one of the critical determinants of extrasynaptic glutamate dynamics (2,8,9,11,30). Thus, we evaluated the intensity of PF inputs required to induce detectable levels of glutamate signals and examined the spatial distribution of extrasynaptic glutamate dynamics in response to a minimal level of PF inputs.…”
Section: Extrasynaptic Glutamate Dynamics Are Locally Induced By a Smallmentioning
confidence: 99%
“…However, glutamate has also been suggested to escape from the synaptic cleft, generating extrasynaptic glutamate dynamics (often referred to as glutamate spillover) (1)(2)(3)(4). Extrasynaptic glutamate dynamics has been implicated in the activation of extrasynaptic glutamate receptors via volume transmission to regulate a variety of important neural and glial functions including synaptic transmission (5,6), synaptic plasticity (7), synaptic crosstalk (8)(9)(10)(11), nonsynaptic neurotransmission (12,13), neuronal survival (14), gliotransmitter release (15)(16)(17), and hemodynamic responses (18)(19)(20).…”
mentioning
confidence: 99%
“…In the cerebellum and hippocampus, it has been shown that activity-dependent release of glutamate can overcome uptake systems and lead to spillover-induced inhibition of GABAergic synaptic transmission via activation group II/III mGluRs (Mitchell and Silver, 2000;Semyanov and Kullmann, 2000). Furthermore, glutamate spillover inhibits glutamatergic transmission in the cerebellum via group I mGluR-induced endocannabinoid signaling (Marcaggi and Attwell, 2005;Wadiche and Jahr, 2005). In the present study, it was found that although mGluR5 (MPEP, 10 M) and broadspectrum mGluR antagonists (LY341495, 100 M) had no effect on single evoked IPSCs, they increased IPSCs evoked by repetitive stimulation at rates within the range of firing rates encountered in vitro (Sanchez and Ribas, 1991;Ogawa et al, 1994).…”
Section: Glutamate Spillover Drives Endocannabinoid Signalingmentioning
confidence: 99%